Mechanical, physical, and chemical characterization of Ti-35Nb-5Zr and Ti-35Nb-10Zr casting alloys - Roselino Ribeiro, Ana Lucia [UNESP]; Caram Junior, Rubens; Cardoso, Flavia Farias; Fernandes Filho, Romeu Belon [UNESP]; Vaz, Luis Geraldo [UNESP] (Springer, 2009)
Titanium is used due its excellent properties in medical and dentistry areas. With the objective of exploiting better mechanical properties, not altering its biocompatibility, it was intended to add niobium and zirconium to the titanium, being formulated two alloys Ti-35%Nb-5%Zr (alloy 1) and Ti-35%Nb-10%Zr (alloy 2) wt% produced by an arc melting method. The chemical analysis of the samples was accomplished by X-ray fluorescence, and the microstrutural evaluation by scanning electron microscopy and X-ray diffraction. The mechanical tests were: Vickers hardness, tensile strength, mechanical cycling, and fracture analysis. The results allowed characterizing the alloy 1 as alpha + beta type and the alloy 2 as beta type. It is found that the alloy 1 presented larger hardness and smaller tensile strength than the alloy 2. The fractures, after the tensile test, were of the ductile type and, after the mechanical cycling, they were of the mixed type for both alloys.